Does central bank communication really lead to better forecasts of policy decisions? new evidence based on a Taylor rule model for the ECB - Sturm, Jan-Egbert 1969-; Haan, Jakob de 1960- (CESifo working paper, 2009)
Nowadays, it is widely believed that greater disclosure and clarity over policy may lead to greater predictability of central bank actions. We examine whether communication by the European Central Bank (ECB) adds information compared to the information provided by a Taylor rule model in which real time expected inflation and output are used. We use five indicators of ECB communication that are all based on the ECB President's introductory statement at the press conference following an ECB policy meeting. Our results suggest that even though the indicators are sometimes quite different from one another, they add information that helps predict the next policy decision of the ECB. Furthermore, also when the interbank rate is included in our Taylor rule model, the ECB communication indicators remain significant. -- ECB ; central bank ; communication ; Taylor rule